(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The essay begins with a reflection on the question of whether it is profitable or not to consider Joyce a modernist writer in view of his “medieval” approach to aesthetics. Alternatively, it discusses the possibility of reading Joyce also in the light of some affinities between his “literary discoveries” and certain developments of contemporary science – namely relativity and quantum physics. Hence the necessity to revisit his writings in translation by paying attention to his attempts to write in ways that would, on the one hand, defy and debunk tradition, and on the other set a path for a new type of fruition and translation strategies suited to the différence of Joyce. Examples are given from the author’s translations of specific passages in Ulysses and Finnegans Wake highlighting the need for a peculiar flexibility in translation appropriate to the eternal changeability of Joyce’s textuality. Il saggio parte dall’interrogativo se sia proficuo o meno considerare Joyce uno scrittore modernista alla luce del suo approccio “medievale” all’estetica. Viene quindi discussa la possibilità di leggerne l’opera anche alla luce di alcune affinità tra le sue “scoperte letterarie” e alcuni sviluppi della scienza coeva – in particolare la relatività e la fisica quantistica. Da qui la necessità di rivisitare i suoi scritti tramite una lente traduttiva che consenta di prestare attenzione al tentativo di scrivere per sfidare, da un lato, la tradizione, e dall’altro aprire la strada a un nuovo tipo di fruizione e a strategie di traduzione adatte alla différence di Joyce. Sono forniti e discussi esempi di traduzioni da parte dell’autore di passi specifici dell’Ulisse e di Finnegans Wake in cui si evidenzia la necessità di una peculiare flessibilità traduttiva, adeguata all’eterna mutevolezza della testualità joyciana.